Material culture of the people of southeastern Panama : based on specimens in the United States National Museum (2022)
eng: Southeastern Panama is historically the oldest region of continental America. Here, early in the sixteenth century, in so-called Darien, the country extending from the Chepo or Bayano River on the Pacific slope near the Canal Zone southeastward to the Atrato River on the Caribbean slope near the Colombian border, were made the first Spanish explorations and settlements. Within a few years, indeed as early as 1518, the Spanish were forced to leave Darien because of conflict with native tribes and, later, with English buccaneers and freebooters. They then established themselves at Panama City, more than 100 miles farther west along the Pacific coast.